Extraction and Characterization of Nano-cellulose from Local Waste Paper Egg Trays - Ruiwen Yu; Prabhakar M. N.; Dong Woo Lee; Jung-ll Song (Journal of Natural Fibers, 2022)
Current research focused on local bio-waste paper egg trays for the extraction of nano cellulose via common chemical method followed by mechano-ball milling process. The characteristic features of extracted cellulose were analyzed by scanning electron microscopy coupled with energy-dispersive x-ray spectroscopy (SEM-EDX), fourier transform infrared spectroscopy (FTIR), x-ray diffraction (X-RD), elemental analysis, thermogravimetric analysis (TGA), and micro calorimeter. The optimized alkali-acid (NaOH(10%)-H2SO4(65%)) is the best percentage for the extraction of cellulose in a nano-form with almost no impurities as clearly described through SEM (~500 nm), FTIR further strengthens the O-H, C-H, C = O, C-O(acyl) and C-O (alkoxy) bond peaks at 3660–2900, 3472, 1656, 1315, and 1026 cm−1, and XRD analysis showed the % crystallinity 88.2 and average grain size 4 nm. Furthermore, TGA and micro calorimeter analysis exhibited significant thermal performance (~19 wt.% @700°C) and flame retardancy (pHRR 132 kJ/g). EDX and elemental analysis further supported the extracted cellulose. Overall, this investigation provides an economic and easy way of producing nano-cellulose that can replace the commercial nano-cellulose as reinforcement for natural fiber composites.